Methods and explanations in the study of human actions and their environmental effects. CIFOR/WWF Special Publication. - Vayda, A.P. (1996)
Andrew P. Vayda, drawing on his long experience in studying the relations between people and their environments, addresses here the question of how human influences can be better incorporated into ecological studies. Citing relevant sources from the literature of philosophy as well as social and biological science, he argues that we should be guided in our research by the goal of giving causal explanations of concrete human behaviour and its concrete environmental effects. Existing theories and models may have a role in guiding such efforts, but developing or testing the theories and models need not be made the main objective.Before illustrating his advocated approach with various studies (including his own research in Indonesian forests), Professor Vayda considers other approaches and indicates problems with them because of their failure to give due consideration to the chains of causally connected events leading to specific actions and their effects. Among the problematic approaches are those which assume that human behaviour affecting the environment is governed by basic conceptualisations or values concerning nature or the environment. Certain systems approaches to the study of environment-related human behaviour are also critically examined.